Effects of Configurations of Conductor Wire in A Helix Coil Type Ozone Generator - Leejongpermpoon, Sutee; Yutthagowith, Peerawut (My University, 2018)
This article presents the effects of configurations of helix-coil wire electrodes in an ozone generator with length 20cm. The effects of the configurations to the ozone production in water, i.e. air gap, wire conductor diameter, wire pitch, and turn number of wire were analyzed by using FEM simulation program. Then, to confirm the validity of the effects, various settings including setting pitch length between 0 and 40mm and the turn number of wire between 5 and 331 were performed in the simulation. Finally, the experiments are performed according to the simulation setting with the supplied voltage of 5.8 kV and the frequency of 50Hz. The results showed that the most optimized configuration has the pitch length approximately 3 times of the wire diameter.
Keywords: Electrode; Helix Coil; Ozone